Increased expression of cardiac IL-17 after burn - Sasaki Jennifer R; Rani Meenakshi; Zhang Qiong; Oppeltz Richard F; Schwacha Martin G (BMC, 2010)
Abstract Background Cardiac dysfunction is a common complication associated with major burns. While recent findings have linked the Th-17 T-cell response to the development of autoimmune myocarditis, the role of IL-17 and the Th-17 T-cell response in the development of post-burn cardiac dysfunction remains unknown. Methods Male C57BL/6 mice were subjected to a major burn (3rd degree, 25% TBSA) or sham treatment. Three hours after injury plasma and tissue (i.e., heart, lung, liver, small intestine) samples were collected and analyzed for the expression of Th-17 cytokine (i.e., IL-6, IL-17, IL-22, IL-23, TGF-β) levels by ELISA. Results Cardiac tissue levels of the Th-17 cytokines, IL-6, IL-17 and IL-22 were significantly elevated at 3 hrs after burn as compared to sham levels. IL-17 was analyzed 1, 3 and 7 days after burn and showed a return to baseline levels and without a difference in the burn group. Burn-induced alterations in the level of these cytokines in plasma or other tissues were not evident. The cardiac Th-17 cytokine response after burn injury was specific, as cardiac levels of Th-1 (IFN-γ) and Th-2 (IL-10) cytokines were not significantly affected after injury. The cardiac Th-17 response correlated with a significant increase in Troponin levels at 3 hr. after burn. Conclusion These findings indicate that early after burn, cardiac tissue is associated with significantly elevated levels of Th-17 cytokines. The early Th-17 response after burn appears to be specific for cardiac tissue and may promote myocardial inflammation and dysfunction associated with this form of trauma.